The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0087865
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Resveratrol and Lipoic Acid, or Their Synthetic Combination, Enhances Neuroprotection in a Rat Model of Ischemia/Reperfusion

Abstract: The present study demonstrates the benefits of combinatorial antioxidant therapy in the treatment of ischemic stroke. Male Sprague-Dawley rats were anaesthetised and the middle cerebral artery (MCA) was occluded for 30 minutes followed by 5.5 hours of reperfusion. Pretreatment with resveratrol 30 minutes prior to MCA occlusion resulted in a significant, dose-dependent decrease in infarct volume (p<0.05) compared to vehicle-treated animals. Neuroprotection was also observed when resveratrol (2×10−3 mg/kg; iv) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Resveratrol also regulates the expression of various proteins associated with oxidative stress and energy metabolism in focal cerebral ischemia (25). Furthermore, resveratrol can enhance the neuroprotection when coadministrated with lipoic acid in cerebral ischemia (24). In the present study, we first established the model of BCCAO, and then we found that resveratrol pretreatment could protect the brain from ischemic injury, which is associated with its antiapoptotic effect.…”
Section: A B C Dmentioning
confidence: 50%
“…Resveratrol also regulates the expression of various proteins associated with oxidative stress and energy metabolism in focal cerebral ischemia (25). Furthermore, resveratrol can enhance the neuroprotection when coadministrated with lipoic acid in cerebral ischemia (24). In the present study, we first established the model of BCCAO, and then we found that resveratrol pretreatment could protect the brain from ischemic injury, which is associated with its antiapoptotic effect.…”
Section: A B C Dmentioning
confidence: 50%
“…Despite the ongoing advances in the field of stroke research, consequences of death and disability have remained considerable throughout the world and delivery of successful therapeutics is still a challenge [23,26]. Treatment outcomes for ischemic events involve the restoration of blood supply to an ischemic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published the detailed methodology for occlusion of the middle cerebral artery [12,13,32,33] in both permanent (pMCAO) and transient (tMCAO) models.…”
Section: Transient and Permanent Middle Cerebral Artery Occlusion (Tmmentioning
confidence: 99%
“…Thus, there has been a recent interest in the use of co-drugs as a therapeutic approach in various pathologies [9,10]. The development and administration of a co-drug, containing lipoic acid (LA) covalently linked to another compound, have been demonstrated to have a greater efficacy/potency compared to the administration of a mixture of the two drugs [11,12,13,14,15,16]. The antioxidant LA, is a known free radical scavenger [17,18], and many researchers have shown that in several different stroke models administration of lipoic acid on its own can be neuroprotective but only at relatively high doses [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation